2004
DOI: 10.1124/jpet.104.075077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabotropic Glutamate Receptor Responses at Segmental and Descending Inputs to Motoneurons in Neonatal Rat Spinal Cord

Abstract: We compared the contribution of metabotropic glutamate receptors (mGluRs) to the generation and modulation of synaptic responses elicited in intracellularly recorded L5 motoneurons from neonatal rats by segmental and descending fibers. Dorsal root (DR) stimulation at high intensity (C-fiber strength) evoked long latency (2-5-s) depolarization in addition to early monosynaptic and polysynaptic responses. Stimulation of the descending ventrolateral funiculus (VLF) failed to evoke a late response in the same moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…The present investigation as well as previous studies, have demonstrated that neither broad spectrum nor specific mGluR antagonists have significant effects per se on spinal MNs or VLF-MN synapses (Marchetti et al, 2003;Arvanian et al, 2005;Iwagaki and Miles, 2011) suggesting an absence of endogenous, tonically activated mGluRs. Here, we show that mGluR activation can be induced by increasing synaptic glutamate concentration with the glutamate uptake blocker TBOA or high frequency stimulation of presynaptic axons that revealed the extrasynaptic localization of mGluRs at synapses impinging onto lumbar MNs.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The present investigation as well as previous studies, have demonstrated that neither broad spectrum nor specific mGluR antagonists have significant effects per se on spinal MNs or VLF-MN synapses (Marchetti et al, 2003;Arvanian et al, 2005;Iwagaki and Miles, 2011) suggesting an absence of endogenous, tonically activated mGluRs. Here, we show that mGluR activation can be induced by increasing synaptic glutamate concentration with the glutamate uptake blocker TBOA or high frequency stimulation of presynaptic axons that revealed the extrasynaptic localization of mGluRs at synapses impinging onto lumbar MNs.…”
Section: Discussionsupporting
confidence: 48%
“…As previously shown by our group ( Lenschow et al, 2016 ), VLF-EPSCs exhibit paired-pulse facilitation (PPF) with this stimulation paradigm ( Figures 1A1–A3 ). In 1 week old rat pups, MCPG, a broad spectrum mGluR antagonist has been shown to block the late component of dorsal root response in lumbar MNs but failed to affect VLF-induced responses ( Arvanian et al, 2005 ). We observed a similar lack of effect of 200 μM MCPG on both VLF-EPSC amplitude ( Figures 1A1,A4 ) and the PPF ratio (VLF-EPSC2/VLF-EPSC1 = 1.3 ± 0.3 in control condition and 1.3 ± 0.3, n = 18 in the presence of MCPG, p = 0.5, Wilcoxon matched-pairs test) in P1-P3 mice.…”
Section: Resultsmentioning
confidence: 99%
“…In evaluating glutamatergic transmission, it is important to recognize that the initial response measured intracellularly from motoneurons consists of two components, one mediated by α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionate (AMPA)/kainate receptors, and a slightly slower one mediated by N ‐methyl‐ d ‐aspartate (NMDA) receptors (NMDARs) (Ziskind‐Conhaim, 1990; Arvanian & Mendell, 2001a). A third component, mediated by metabotropic glutamate receptors, appears much later, and requires high‐intensity stimuli activating C‐fibers (Arvanian et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%